Vertical ozone profiles in the atmosphere over the Antarctic Peninsula and Kyiv by Umkehr observations - Andrienko, Yu.; Milinevsky, G.; Danylevsky, V. (Ukrainian Antarctic Journal, 2021)
The Umkehr observations over Kyiv (Ukraine) and Antarctic Peninsula areas were processed for the first time to retrieve and analyse the vertical distribution of ozone. The Umkehr observations have been pre-processed using the UMK92 software package proposed by the World Ozone and UV-radiation Data Centre (WOUDC). The set of the calculated vertical ozone profiles for Kyiv–Goloseyev station (2011–2020) and Akademik Vernadsky station (2005–2009) has been obtained. Analysis of ozone profiles observed with Dobson spectrophotometer D040 indicates that the maximum ozone concentration is located in the altitude range of 15–25 km with an average height of 19.8 ± 1.4 km. It corresponds to the layer of maximum ozone concentration in the mid-latitude stratosphere. The maximum ozone partial content in Dobson Units per the layers (DU/layer) with thickness of 5 km altitude for most of the years are of 60–80 DU/layer. There are also days with the maximum ozone content significantly larger than an average. A characteristic feature of the profiles is that the lower ozone content occur in summer and autumn months in the range of 60–75 DU/layer. The winter and spring profiles demonstrate higher ozone values at the maximum. To analyse the vertical profiles of ozone in Antarctic Peninsula area, we use Umkehr data from observations at the Akademik Vernadsky station with the Dobson D123 spectrophotometers in 2005–2009. The data processing and the calculation of the vertical ozone profiles was provided according to the methodology developed at the Kyiv–Goloseyev station. It is shown that the ozone profiles at the Akademik Vernadsky station vary in a wide range of values of the maximum ozone concentration from 40 to 110 DU/layer. Ozone content at maximum of vertical distribution was changing dramatically from day to day in the Antarctic region during the ozone hole period.